ADSC-exo@MMP-PEG smart hydrogel promotes diabetic wound healing by optimizing cellular functions and relieving oxidative stress. (December 2022) - Jiang, Tao; Liu, Siju; Wu, Zihan; Li, Qianyun; Ren, Sen; Chen, Jing; Xu, Xiang; Wang, Cheng; Lu, Cuifen; Yang, Xiaofan; Chen, Zhenbing
Abstract: Diabetic wound complications are financially costly and difficult to heal in worldwide. Whereas the therapies of diabetic wound, such as wound dressing, endocrine therapy or flap-transplantations, were not satisfied. Based on our previous study of exosome secreted by adipose-derived stem cell (ADSC-exo), we loaded ADSC-exo into the matrix metalloproteinase degradable polyethylene glycol (MMP-PEG) smart hydrogel. Physical and chemical properties of ADSC-exo@MMP-PEG smart hydrogel were tested by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), weight loss examination, etc. As the hydrogel degraded in response to MMP, ADSC-exo was released and subsequently enhanced cell function via Akt signaling. Moreover, treatment with ADSC-exo@MMP-PEG smart hydrogel significantly relieved the H2 O2 -induced oxidative stress, which was widely recognized as a major cause of diabetic wound nonhealing. Similar results were achieved in mice diabetic wound models, in which the ADSC-exo@MMP-PEG treatment group displayed a significantly accelerated wound healing. To summarize, the present smart hydrogel with enzyme-response and exosome-release was proved to be benefit for diabetic wounds healing, which provides a reliable theoretical basis for application of ADSC-exo in treatment of diabetic wounds. Graphical abstract: Image 1 Highlights: Loading ADSC-exo into PEG formed a smart hydrogel. The smart hydrogel delivered exosome in response to MMP-2. The smart hydrogel promoted diabetic wound healing by optimizing cellular functions.